Indonesian Micromelum minutum Leave Extracts and Their Cytotoxic Activities toward Breast Cancer Cell Lines - Ratna Asmah Susidarti; Edy Meiyanto; Muthi' Ikawati; Normaidah; Nurramadhani Armada Sida (Institute for Research and Community Services (LPPM) ITB, 2021)
Isolation and identification of compounds and pharmacological activity of the Micromelum minutum grown in some countries has been done, but the Indonesian M. minutum has not been studied, either phytochemically or pharmacologically. This study aimed to determine the cytotoxic activity of Indonesian M. minutum leave extracts toward MCF-7 and 4T1 breast cancer cell lines. The leaves were obtained from M. minutum grow in Bantimurung National Park, Bulusaraung, South Sulawesi, and then were macerated gradually in hexane, ethyl acetate, and methanol. The cytotoxic activity of obtained extracts was determined by MTT assay. The extraction yielded hexane (HEM), ethyl acetate (EEM), and methanol (MEM) extracts of 2.65, 6.12, and 6.49%, respectively. HEM was the most potent extract with IC50 values of 148 and 87 µg/mL on MCF-7 and 4T1 cells, respectively, followed by EEM (185 and 170 µg/mL). MEM possessed a weak potency with an IC50 value of 384 µg/mL on MCF-7 cells and was not toxic toward 4T1 cells. Therefore, HEM is important to be further investigated for its active constituents.